Climate Change and Farmers’ Household Financial Vulnerability: Evidence From China - Yang, Sen; Zou, Kai; Lei, Tianyi; Ni, Zehua; Yang, Jingyi (Frontiers in Environmental Science, 2022)
Climate change is one of the most severe threats to human survival and a significant factor influencing financial stability. Different from previous studies, this paper investigates the economic impact of climate change at the micro level based on data from China Meteorological Administration database, and China Household Finance Survey (CHFS) 2017 released in 2019. The empirical findings indicate that climate change contributes to the financial vulnerability of farmers' households, which is confirmed following robustness tests. The mechanism analysis reveals that climate change has effects on rural households' financial vulnerability via farmers' health, credit availability, and agricultural output. Furthermore, the effect of climate change on farmers' household financial vulnerability (HFV) is more pronounced in farmers with lower education levels. The changes in temperature and precipitation show different intensity effects in different areas, but all of them provide reasonable heterogeneity mechanisms. This paper's policy value is demonstrated by the fact that it uncovers the effects of climate change on farmers' HFV, information that may be useful for addressing climate change and rural financial stability.